Ethical Foundations of Knowledge in Hasyim Asy’ari’s Thought: Relevance for Pesantren Andragogy - Jasminto (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2024)
This study aims to analyze the ethical foundations of knowledge in the thought of KH Hasyim Asy’ari and their relevance to pesantren andragogy through a literature-based research approach. The study is grounded in the view that pesantren education, particularly for adult learners, is constructed upon a strong and systematic tradition of scholarly ethics. Employing a qualitative philosophical approach, this research uses a literature review method by examining the works of KH Hasyim Asy’ari-especially Adab al-‘Ālim wa al-Muta‘allim-along with relevant secondary literature in the fields of Islamic philosophy of education and andragogy theory. The analysis reveals that the ethical foundations of knowledge in KH Hasyim Asy’ari’s thought emphasize sincerity, proper conduct toward teachers and knowledge, moral discipline in the learning process, and the integration of knowledge, practice, and moral character. These principles demonstrate a conceptual correspondence with the characteristics of pesantren andragogy, which stress self-awareness, ethical responsibility, and experiential learning among adult learners. This study concludes that KH Hasyim Asy’ari’s concept of scholarly ethics is not merely normative-theological in nature but also holds philosophical and pedagogical significance as a conceptual foundation for the development of pesantren-based andragogy rooted in the Islamic scholarly tradition.